Eryngium Species as a Potential Ally for Treating Metabolic Syndrome and Diabetes - Pérez-Muñoz, Eréndira Patricia; Antunes-Ricardo, Marilena; Martínez-Ávila, Mariana; Guajardo-Flores, Daniel (Frontiers in Nutrition, 2022)
Medicinal plants possess natural compounds that can be used as an alternative for synthetic medicines that may cause long-term side effects on patients such as neurocognitive effects, muscular and hepatic toxicity. Metabolic Syndrome is associated with increased risk of several diseases such as diabetes, cardiovascular disease, dyslipidemia, and hypertension thus, becoming the greatest challenge as a growing public health concern worldwide. Latin-American countries possess a wide diversity of medicinal plants that have been used to treat different health conditions since pre-Hispanic times. Eryngium spp. has been studied due to their beneficial properties mainly to treat diabetes, dyslipidemia, blood pressure, and digestive problems. This review gives an update mainly on the pharmacological activities of the Eryngium spp., summarizing the biological activities and plausible mechanism of action of their bioactive components toward metabolic syndrome. For instance, flavonoids and tannins proved to increase the levels of HDL and reduced the levels of VLDL, LDL. On the other hand, phenolic acids improved glucose metabolism through the inhibition of phosphoenolpyruvate carboxykinase and glucose 6-phosphatase (G6Pase) and reestablished the impaired activity of enzymes related to glucose oxidation and glycogen synthesis. The terpenes and sesquiterpenes like β-farnese, β-pinene, and calamenene exhibited a protective effect by reducing the oxidizing damage by the regulation of the Reactive Oxygen Species (ROS). Saponins controlled the dyslipidemia by reducing the serum concentrations of lipids, triglycerides and total cholesterol. Finally, the aerial parts of Eryngium had the capacity of inhibiting dietary carbohydrate digestive enzymes, thus controlling glucose levels. The Eryngium plant is normally consumed as an infusion to obtain the benefits of the plants, however novel technologies such as cavitation, ultrasound assisted, microwave assisted, and supercritical fluid have been applied to improve the extraction yields and selectivity of bioactive compounds. The common treatment to control diabetic dyslipidemia are synthetic medicines such as metformin and ezetimibe, which allows the regulation of glucose, cholesterol and insulin resistance. However, patients that take these medications may present side effects such as muscular toxicity, hepatic toxicity, neurocognitive effects, just to name a few. More studies regarding the efficacy and safety of the use of traditional medicinal herbs are required. However, these materials may be used in the treatment of diabetes related conditions to ensure life quality and reduce side effects among the diabetic population